Beyond the Second Sophistic : adventures in Greek postclassicism - Whitmarsh, Tim (University of California Press, 2013)
What happened to Greek literature after the classical period - when Sophocles, Plato, and Demosthenes were just a memory? Post-classical Greek culture has usually been thought of as dominated by aristocratic elites obsessed with preserving links to the past. This book proposes a very different model. Covering popular fiction, poetry, and Greco-Jewish material, it argues for a rich, dynamic, and diverse culture that cannot be reduced to a simple model of continuity.